Resistance and sensitivity of Fasciola hepatica against four active anthelminticprinciples in guinea pigs (Cavia porcellus), Cajamarca, Peru - Ravines, José (2024)
The study aimed to evaluate the efficacy of four anthelmintics in the control of Fasciola hepatica at the Estación Experimental del Instituto Nacional de Innovación Agraria (INIA), Baños del Inca, Cajamarca, Perú. Forty guinea pigs from 5 to 12 months of age of the Inka line, naturally infected with F. hepatica (≥1 HPG), not dewormed in the last 4 months, under the same management and feeding system were used. The animals were distributed into four groups (n=10): triclabendazole (25 mg/kg) and closantel (20 mg/kg) orally, clorsulon + ivermectin (15 mg/kg based on clorsulon) and nitroxinil (50 mg/kg) subcutaneously. The parasite load was determined on days 0 and 30 post-dosing. The Egg Count Reduction Test determined an efficacy of 0% for triclabendazole and 100% for closantel, clorsulon + ivermectin, and nitroxinil. It is concluded that F. hepatica is resistant to triclabendazole and sensitive to closantel, clorsulón + ivermectin and nitroxinil in guinea pigs from INIA-Cajamarca.